(untitled) (Research, Society and Development, 2021)
Georgian cabbage (Brassica oleracea L. var. acephala) is a vegetable belonging to the Brassicaceae family, an annual or biennial shrub, whose consumption in Brazil has increased due to new research on its nutritional properties. The aim of this study was to monitor the development of kale from germination in the causes of variation. The experimental study was conducted in the greenhouse of the State University of Alagoas campus I from October to December 2020. The seeds used to calculate the germination index (GI) and germination speed index (IVG) were sown. in sowing using carbonized rice husk substrate, 96 cells and 5 seeds were used in each, totaling 480 seeds. In pots, the experimental design was completely randomized, with four treatments and five replications. The pre-harvest variables evaluated were: plant height (HP), stem diameter (DC) and number of leaves (NF), in post-harvest: fresh mass (MF), dry mass (DM), size root (TR) and full size (TT). Data were recorded weekly and then statistically analyzed using the Agroestat program to verify the analysis of variance - ANOVA and the comparison of means, using the Tukey test at 5% probability. Germination showed good results and there was a significant difference between treatments, with goat manure showing the best result.